Organisation’s support influences the acceptance and use of e-learning among academic staff of higher learning Institution in Sabah - Kee Y Sabariah Bte Kee Mohd Yussof; Nor Shahzanani Sudirman; Mahadirin Ahmad; Jalihah Md Shah; Jurry Foo; Ramlah Daud (UPSI, 2025)
E-learning refers to the use of electronic media, digital technology tools such as laptop, smart phone, and interactive Tv in teaching and learning process. Nowadays, it is undeniable that most higher learning institutions choose to implement E-learning in their education system which it becomes the alternative to the traditional learning method in teaching. Through the implementation, education institutions have the potential in establishing more open and flexible teaching and learning environment. However, to drive the a wholistic implementation of E-learning in higher learning institutions, the aspect of organisational support in terms of technicality and infrastructure facilities should be prioritised so that all parties especially the academic staffs can easily adapt and use it. Therefore, this pilot study is aimed to study the level of E-learning usage through the Unified Theory of Acceptance and Used of Technology (UTAUT) Model and the influence of organisational support on the E-learning implementation among academic staff in Sabah. The findings of simple regression analysis showed the influence of organisational support at 66 percents on the implementation of E-learning among the academic staffs, with the model’s contribution (R2=.44, k=.00). the findings found that organisational support is the significant factor in influencing the acceptance and implementation process of Elearning among the academic staffs of higher learning institutions in Sabah. Thus, this study proposes each learning institutions in Sabah to increase the organisational support especially in technicality and infrastructure to empower E-learning platforms in future.